The inclusion of specific texts for the improvement of employability in Bachelor’s degree courses - Álvarez Torres, Vanesa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Many university students are faced with the job search for the first time when they finish their Bachelor’s degree and, moreover, without ever having written a cover letter or a résumé. A transversal training on this type of issues should be present in undergraduate studies, regardless of the area of knowledge. In this proposal, we present the integration of this type of specific texts in the syllabus of three different subjects. To do so, we explain the methodology used, the results obtained and the conclusions of this teaching proposal.